Relevansi Tujuan Pembelajaran Pendidikan Agama Islam untuk Membangun Karakter Religius Siswa di Sekolah (Systematic Literature Review) - Miftahul Alimin; Hikmatin Kamilah; Shofwatul Widad (Jurnal Multidisiplin Ibrahimy, 2024)
This study aims to describe Islamic religious education learning objectives' relevance to building students' religious character in schools. The design of this research is a systematic literature review (which refers to specific guidelines). Researchers searched for and took literature from Google Scholar and Garuda Research and Technology. The criteria for selecting literature is journal articles resulting from field research, published between 2017-2021 and written in Indonesian. The literature screening found 30 articles. After reading the title and abstract, 15 articles were excluded from the review, and five articles were excluded after reading the entire text. The remaining ten texts were included for review. The research concludes that the purpose of Islamic religious education is the foundation for the formation of students' religious character, especially changes in students' knowledge and behaviour. They are achieving goals through habituation, exemplary and enforcement of rules.